Avaliação de parâmetros de desempenho de um motor de ignição por compressão operando em modo dual-fuel (diesel-etanol) - Vogt, Rafael (2020)
The ethanol, a renewable and highly productive fuel in Brazil, appears as one of the main fuels in order to comply with rigorous legislation on emissions of pollutants and greenhouse gases on vehicle engines, agricultural machinery, or power generation. The combustion strategy dual-fuel mode (Diesel / Ethanol) may reduce the pollutant emission rates, as well as diesel consumption. This study intended to evaluate performance and emission parameters of a combustion engine with dual mode operation system using two different methods. Combustion mode RCCI (Reactivity Controlled Compression Ignition), using diesel as high reactivity fuel and ethanol as low reactivity fuel. Fumigation combustion, with ignition provided by pilot diesel injection. The experimental tests began with the mapping of the engine operating in Diesel cycle in order to obtain the baseline test, in IMEP loads 5 and 7 bar and fixed rotation of 1800 rpm, serving as comparative reference for subsequent tests. The tests with dual fuels changed in points with RCCI combustion and in dual-fuel by fumigation. The results showed a maximum substitution from diesel to ethanol in 92%, reaching a reduction in NOx emissions up to 93%. In contrast there was an increase in HC and CO emissions, and an increase in specific consumption, penalizing the efficiency indicated between 13 to 23% in the tests performed. Thus, it was possible to prove the technical feasibility of using dual-fuel combustion modes as a possible option to reduce environmental impact and comply with requirements imposed by regulatory standards.